Idiopathic Immunodeficiency in Cytomegalovirus Reactivation: A Rare Case - Dewi Indiastari; Tri Wahyudi Iman Dantara; Neila Raisa (International Journal of Science and Society, 2022)
Idiopathic CD4 lymphocytopenia (ICL) is a rare condition characterized by an unexplained deficit of circulating CD4 T cells leading to increased risk of serious opportunistic infections. Reactivation and severe symptomatic CMV is also a rare case, except in immunocompromised patient. Patient concerns are 36-year-old male patient complained seizure, fever, cough, and dyspnea. History of chronic urticaria and prolonged Mebhydrolin consumption. HIV was negative. CD4 was low. Diagnosis in this case is Viral encephalitis, Viral pneumonitis, CMV reactivation, hemophagocytic lymphohistiocytosis immunodeficiency state. The results in this study indicate that the patients were treated with conventional therapies for Severe CMV infection with Acyclovir. Steroid was given for the last five days. The first day after administration of therapy showed clinical and laboratory improvement. Laboratory values returned to normal values on the fifth day of therapy. Since the second day after the therapy was given, the patient had no complaints. In cases of CMV reactivation, an immunodeficiency condition should be suspected. A comprehensive history, physical examination, laboratory and radiological examination, adequate therapy and and policy support are required to establish a definite diagnosis and reduce the risk of mortality.